2011
DOI: 10.1093/humrep/der223
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovarian morphology in adolescents with regular menstrual cycles is associated with elevated anti-Mullerian hormone

Abstract: These data confirm that PCOM in healthy non-hyperandrogenic girls with regular menstrual cycles is prevalent and is not associated with hyperandrogenism. The elevated AMH and lower FSH levels observed in healthy girls with regular menses and PCOM suggest that this ovarian pattern is secondary to a larger number of 2-5 mm follicles. An elevated AMH level is suggestive of the presence of PCOM during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 47 publications
7
58
1
2
Order By: Relevance
“…AMH concentrations reflect the number of antral follicles and are often elevated in adult women with PCOS. Available data are inconsistent regarding the usefulness of AMH in the diagnosis of PCOS among adolescent girls [92][93][94][95][96] . (2) Further, a multifollicular pattern, which is defined by the presence of large follicles distributed throughout the ovary, does not have a relationship with hyperandrogenism, is more common in adolescents, and should not be considered a pathological finding (Level C).…”
Section: What Hormonal Findings Are Associated With Polycystic Ovaries?mentioning
confidence: 99%
“…AMH concentrations reflect the number of antral follicles and are often elevated in adult women with PCOS. Available data are inconsistent regarding the usefulness of AMH in the diagnosis of PCOS among adolescent girls [92][93][94][95][96] . (2) Further, a multifollicular pattern, which is defined by the presence of large follicles distributed throughout the ovary, does not have a relationship with hyperandrogenism, is more common in adolescents, and should not be considered a pathological finding (Level C).…”
Section: What Hormonal Findings Are Associated With Polycystic Ovaries?mentioning
confidence: 99%
“…Villarroel and cols. (40), from our group, reported that girls with PCOM have higher AMH levels than girls without PCOM (72.5 ± 6.1 vs. 33.4 ± 2.6 pmol/L; P < 0.0001), and lower FSH levels (5.4 ± 0.3; 6.2 ± 0.2 mUI/ml; P < 0.036). AMH levels positively correlated with the 2-5 mm follicle number, and AMH levels above 60.15 pmol/L had a sensitivity and specificity of 64.0 and 89.8%, respectively, to diagnose PCOM by the Rotterdam criteria (AUC = 0.873).…”
Section: Polycystic Ovarian Morphologymentioning
confidence: 67%
“…The hormonal profile associated with the presence of PCOM has shown that this condition, when observed in healthy girls with regular menstrual cycles, is not associated with insulin resistance or hyperandrogenism (40,43,44). However, Mortensen and cols.…”
Section: Polycystic Ovarian Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Many adolescents exhibit physiologic menstrual irregularity and signs of androgen excess (e.g., acne) in the peripubertal period (13). In addition, normative testosterone levels are ill defined in this age group (14), and normal adolescent ovarian morphology overlaps with that of women with PCOS (15,16).…”
Section: Diagnostic Criteriamentioning
confidence: 99%